Sex Hormone Influence on Hepatitis in Young Male A/JCr Mice Infected with Helicobacter hepaticus - Theve, Elizabeth J. (American Society for Microbiology (ASM), 2008)
Hepatitis B virus (HBV), the leading cause of human hepatocellular carcinoma, is especially virulent in males infected at an early age. Likewise, the murine liver carcinogen Helicobacter hepaticus is most pathogenic in male mice infected before puberty. We used this model to investigate the influence of male sex hormone signaling on infectious hepatitis. Male A/JCr mice were infected with H. hepaticus or vehicle at 4 weeks and randomized into surgical and pharmacologic treatment groups. Interruption of androgen pathways was confirmed by hormone measurements, histopathology, and liver gene and Cyp4a protein expression. Castrated males and those receiving the competitive androgen receptor antagonist flutamide had significantly less severe hepatitis as determined by histologic activity index than intact controls at 4 months. Importantly, the powerful androgen receptor agonist dihydrotestosterone did not promote hepatitis. No effect on hepatitis was evident in males treated with the 5α-reductase inhibitor dutasteride, the peroxisome proliferator-activated receptor-α agonist bezafibrate, or the nonsteroidal anti-inflammatory drug flufenamic acid. Consistent with previous observations of hepatitis-associated liver-gender disruption, transcriptional alterations involved both feminine (cytochrome P450 4a14) and masculine (cytochrome P450 4a12 and trefoil factor 3) genes, as well gender-neutral (H19 fetal liver mRNA, lipocalin 2, and ubiquitin D) genes. Hepatitis was associated with increased unsaturated C(18) long-chain fatty acids (oleic acid and linoleic acid) relative to saturated stearic acid. Our results indicate that certain forms of androgen interruption can inhibit H. hepaticus-induced hepatitis in young male mice, whereas androgen receptor agonism does not worsen disease. This raises the possibility of targeted hormonal therapy in young male patients with childhood-acquired HBV.